A comparison method of pid tuning on ward-leonard dc compound motor / Mohd Hamdi Thahrir - Thahrir, Mohd Hamdi (2006)
This paper compared three methods of PID tuning, Ziegler-Nichols, Chien, Hrones and Reswick and Chien et. al. by changing the set value of DC compound motor. The openloop control system observed the optimum parameters for PID tuning to control the speed of Ward-Leonard DC compound motor. The methods developed based on the open-loop tuning rules and tangent method to calculate the vital parameters from the process control, which is process gain, dead time, reaction time and tangent.